Aristóteles y Zubiri: Verdad antepredicativa y verdad real - Conderana Cerrillo, Jesús Manuel (2020)
Nuestro trabajo describe las semejanzas y las diferencias entre la doctrina de Aristóteles y de Zubiri respecto a la concepción de la verdad. Aunque Zubiri insiste en señalar muy explícitamente sus discrepancias con las tesis aristotélicas, no es menos cierto que no difieren tan drásticamente en tesis centrales referidas a la concepción de la verdad. Coinciden en que es preciso que exista una verdad más radical y fundamental para que pueda hablarse de “verdad” y de “error” en sentido propio. Aristóteles llama a esa verdad fundamental “verdad antepredicativa”, Zubiri la identifica con la “verdad real”.
Our work describes the similarities and differences between the doctrines of Aristotle and Zubiri regarding the concept of truth. Although Zubiri insists on highlighting very explicitly his discrepancies with the Aristotelian theses, they do not differ so drastically in the central theses which refer to the concept of truth. They agree that there must be a more radical and fundamental truth so that we can speak of “truth” and “error” in the proper sense. Aristotle names that fundamental truth “pre-predicative truth”, whereas Zubiri identifies it with the “real truth”.
Keywords: Aristóteles; Zubiri, Xavier, -- 1898-1983